The East Asian Economy Post-rebalancing: Domestic Demand-led Growth, Social Security, and Inequality - Kosuke Mizuno (IKAT: The Indonesian Journal of Southeast Asian Studies, 2017)
East Asian, including ASEAN (Association of Southeast Asian Nations), countries have pursued the export-oriented development strategies, attracting foreign direct investment and promoting export-driven growth. However, after the Lehman shock, these countries adopted rebalancing policies from export-driven growth to domestic demand-driven growth. Chinese measures to promote domestic demand since 2008 had succeeded in boosting the economy until 2011 with domestic investments and increase in consumption. Chinese economic growth until 2011–2012 made possible an international commodity boom that resulted in the economic development of Malaysia and Indonesia. However, since 2012, the Chinese economy has been suffering from excess capacity and bad loans, hence ending the international commodity boom. ASEAN countries promptly started rebalancing by cutting back on their reliance on exports and increasing domestic investment and consumption, with variation among the countries. ASEAN countries pursued inclusive policies such as education, medical care, and social security. These policies promoted consumption and investment, helping grow the middle class. However, technological progress, globalization, and market-oriented reforms have also been the driving inequality in many Asian countries in the last two decades, and these forces have changed income distribution through three channels, namely, capital, skill, and spatial bias. Inequality created by conventional development strategies in this region has become the basis for conflicts among the region’s different economic strata. Inequality has had the effect of depressing investment—and thus growth—by fueling economic, financial, and political instability.